Efektivitas Penggunaan Media Pembelajaran Monopoly Game Smart Terhadap Minat Belajar Peserta Didik - Faridatul Umah; Kholis Aniyati (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2024)
This research aims to determine the effectiveness of using Monopoly Game Smart learning media on the learning interest of class V students at MI Miftahul Ulum Sooko Wringinanom Gresik. This type of research is Pre-Experimental with the Static Group Comparison Design model. The population in this study was class V MI Miftahul Ulum Sooko Wringinanom Gresik which consisted of 2 classes totaling 43 students, 10 students were taken per class. The data collection used is in the form of scale and documentation. The data analysis technique used is sensitivity data analysis. The results of the research show that there is a significant difference between the pretest and posttest scores, which means that the effectiveness of using the Monopoly Game Smart learning media is effective in increasing interest in learning mathematics. It can be seen that the average score obtained by experimental class students in the process before being given action treatment (pretest) was 12.9000, which is in the medium category. After using the Monopoly Game Smart learning media, the pretest results in the experimental class obtained an average score of 18.1000, which shows that the average score is in the high category. Based on the calculations that have been carried out, the sig value is known. (2-tailed) of 0.000 < 0.05, it can be concluded that the effectiveness of using the Monopoly Game Smart learning media can increase interest in learning mathematics in class V students at MI Miftahul Ulum Sooko Wringinanom Gresik.